What Drives Warming Trends in Streams? A Case Study from the Alpine Foothills. (8th May 2014) - Lepori, F.; Pozzoni, M.; Pera, S.
Abstract We investigated the effects of climate warming and land‐use changes on the temperature and discharge of seven Swiss and Italian streams in the catchment of Lake Lugano. In addition, we attempted to predict future stream conditions based on regional climate scenarios. Between 1976 and 2012, the study streams warmed by 1.5–4.3 °C, whereas discharge showed no long‐term trends. Warming trends were driven mainly by catchment urbanization and two large‐scale climatic oscillations, the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation. In comparison, independent influences by radiative forcing due to increased atmospheric CO2 were uncertain. However, radiative forcing was predicted to further increase stream temperature (to +3–7 °C), reduce summer discharge (to −46%) and increase winter discharge (to +96%) between the present and 2070–2099. These results provide new insights into the drivers of long‐term temperature and discharge trends in European streams subject to multiple impacts. The picture emerging is one of transition, where greenhouse‐gas forcing is gaining ground over climate oscillations and urbanization, the drivers of past trends. This shift would impress a more directional nature upon future changes in stream temperature and discharge, and extend anthropogenic warming to rural streams. Diffusing future impacts on stream ecosystems would require adaptation measures at local to national scales and mitigation of greenhouse‐gas emissions at the global scale. Copyright © 2014 John Wiley & Sons, Ltd.